Calling Solomon's Bluff: Ethics, Aspect-Perception and the Unity of the Tractatus - Campbell, Michael Walter (Wiley-Blackwell, 2020)
In this paper, I consider how we ought to read the aspect-perception passages in the Tractatus Logico-Philosophicus (TLP) in the light of its ethics. I engage with a recent proposal, of Genia Schonbaumsfeld's, that we should replace the TLP account of aspect-perception with that which Wittgenstein puts forward in the Philosophical Investigations (PI). I show that, far from helping us to grasp the ethical vision contained in the TLP, this proposal obscures it. I go on to draw some conclusions from this as to how to read the TLP in its relation to Wittgenstein's other work..
Keywords: Ludwig Wittgenstein; Tractatus; Tractatus Logico-Philosophicus; TLP